2019
DOI: 10.18343/jipi.24.3.258
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Variability in Leaf of Indonesian Rice Landraces and Its Correlation to Bacterial Leaf Blight Disease Resistance

Abstract: Hawar daun bakteri (HDB) adalah salah satu penyakit utama dan penting pada tanaman padi yang disebabkan oleh bakteri patogen Xanthomonas oryzae pv. oryzae (Xoo), terutama padi sawah irigasi. Morfologi daun menjadi karakter yang menarik untuk diinvestigasi hubungannya dengan intensitas penyakit HDB karena daun merupakan bagian tanaman yang diserang oleh penyakit HDB. Tujuan penelitian ini adalah untuk memperoleh informasi keragaman morfologi daun dan korelasinya dengan penyakit HDB untuk mendukung program perak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…In terms of leaf surface, all of the local varieties observed were hairless. Leaf surface presumably has a close relationship with resistance to leaf blight diseases of which the more hairless the surface, the lower the chance of the diseases [15]. Other findings also explained that some phenotypic traits indeed have a relationship with sheath blight resistance in rice [16].…”
Section: Morphological Traitsmentioning
confidence: 93%
“…In terms of leaf surface, all of the local varieties observed were hairless. Leaf surface presumably has a close relationship with resistance to leaf blight diseases of which the more hairless the surface, the lower the chance of the diseases [15]. Other findings also explained that some phenotypic traits indeed have a relationship with sheath blight resistance in rice [16].…”
Section: Morphological Traitsmentioning
confidence: 93%
“…The shape of the leaves of the rice seedlings observed on the 21st day of growth did not align with the development of the seedlings, indicating that the increase in leaf longevity did not correspond with higher doses of gammaray irradiation. Rohaeni et al (2019) suggested that phenotypic diversity reflects genotypic diversity, which is influenced by environmental diversity and escalating doses. The average number of leaves during the seedling phase was observed to be 4 leaves for all treatments.…”
Section: Number Of Leaves (Pieces)mentioning
confidence: 99%
“…Hal ini disebabkan tingginya kandungan selulosa dan hemiselulosa yang menyebabkan dinding sel kaku dan skelenkim menjadi lebih tebal. Menurut (Rohaeni & Yuliani, 2019), morfologi permukaan daun berkorelasi positif dengan ketahanan terhadap penyakit hawar daun bakteri.…”
Section: Deteksi Keberadaan Rtbvunclassified